Praktyk-opleiding as deel van teologiese opleiding - Van Niekerk, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Training in Practice as Part of Theological Training Many churches in South Africa are considering ways to respond to major national problems such as poverty, HIV/AIDS and violence or crime. Surveys show that most Dutch Reformed congregations are not very skilled in this area, and that the theological education does not have the capability to guide congregations to become involved in a well-researched and well-tested manner. Practice research and practice training are procedures that can be followed to meet this challenge. Where academic work primarily produces publications, practice research leads to actions, products or processes first, with publications as an off-spin. Certain adjustments would be required to make the integration of practice learning and practice research into the theological course possible. An adjustment to our view of theology would be that academic work must be seen as a second order activity, namely reflection on the faith and life of the church, and not as the primary source of knowledge and understanding – as tends to happen if the theological debate is confined to theologians. It would also be necessary to adjust the structure of the academic program to make it possible for academics to do these procedures, and to motivate them to do so.